Life expectancy for community-based patients with heart failure from time of diagnosis. (15th January 2015) - James, Stephanie; Barton, David; O'Connell, Eoin; Voon, Victor; Murtagh, Gillian; Watson, Chris; Murphy, Theodore; Prendiville, Brian; Brennan, David; Hensey, Mark; O'Neill, Louisa; O'Hanlon, Rory; et al.
Abstract: Aims: Heart failure has been demonstrated in previous studies to have a dismal prognosis. However, the modern-day prognosis of patients with new onset heart failure diagnosed in the community managed within a disease management programme is not known. The purpose of this study is to report on prognosis of patients presenting with new onset heart failure in the community who are subsequently followed in a disease management program. Methods and Results: A review of patients referred to a rapid access heart failure diagnostic clinic between 2002 and 2012 was undertaken. Details of diagnosis, demographics, medical history, medications, investigations and mortality data were analysed. A total of 733 patients were seen in Rapid Access Clinic for potential new diagnosis of incident of heart failure. 38.9% (n = 285) were diagnosed with heart failure, 40.7% (n = 116) with HF-REF and 59.3% (n = 169) with HF-PEF. There were 84 (29.5%) deaths in the group of patients diagnosed with heart failure; 41 deaths (35.3%) occurred in patients with HF-REF and 43 deaths (25.4%) occurred in patients with HF-PEF. In patients with heart failure, 52.4% (n = 44) died from cardiovascular causes. 63.8% of HF patients were alive after 5 years resulting on average in a month per year loss of life expectancy over that period compared with aged matched simulated population. Conclusions: In this community-based cohort, the prognosis of heart failure was better than reported in previous studies. This is likely due to the impact of prompt diagnosis, the improvement in therapies and care within a disease management structure. Highlights: Heart failure has been demonstrated in previous studies to have a dismal prognosis. We report on prognosis of patients with new onset heart failure in the community followed in a disease management program. In this community-based cohort the prognosis of heart failure was better than reported in previous studies. This is likely due to prompt diagnosis, the improvement in therapies and care within a disease management structure.